Dysregulation of kynurenine pathway and potential dynamic changes of kynurenine in schizophrenia: A systematic review and meta-analysis. (April 2021) - Cao, Bing; Chen, Yan; Ren, Zhongyu; Pan, Zihang; McIntyre, Roger S.; Wang, Dongfang
Highlights: Forty-two eligible papers with 4, 217 participants were included in the analysis. Lower TRP levels and higher circulating KYN/TRP ratios existed in subjects with SCZ. Lower KYN levels were associated with medication-free persons with SCZ. The KYN levels were higher in subjects with SCZ after antipsychotic treatments when compared with baseline. The current evidence provides valuable insight of the potential roles of KYN pathway in the pathogenesis of SCZ. Abstract: The kynurenine (KYN) pathway is postulated to play various roles in immune system dysregulation of schizophrenia (SCZ). We conducted a meta-analysis to explore the association between six key metabolites of KYN pathway (i.e., tryptophan (TRP), KYN, quinolinic acid (QUIN), and kynurenic acid (KYNA)) and SCZ. Priori Bonferroni adjustments were conducted for multiple comparisons. In total, 42 studies that examined the relationship between the metabolites in KYN pathway mentioned above and SCZ in 4217 participants and nine studies that examined alterations of these metabolites after antipsychotic treatments were included. The results demonstrate that (1) subjects with prescribed medication had significantly higher KYN levels when compared to controls; (2) higher KYN levels in cerebrospinal fluid (CSF), lower plasma KYN levels and higher CSF KYNA levels were associated with SCZ; (3) the KYN levels were higher in subjects with SCZ after antipsychotic treatments when compared with baseline. The evidence provides valuable insight of the potential underlying involvement of the KYN pathway in the pathogenesis of SCZ.